2010
DOI: 10.1021/jp909640g
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Profile of the Interaction between a Monomer or a Dimer of Protegrin-1 in a Specific Binding Orientation and a Model Lipid Bilayer

Abstract: The free energies of adsorption of the monomer or dimer of the cationic β-hairpin antimicrobial peptide protegrin-1 (PG1) in a specific binding orientation on a lipid bilayer are determined using molecular dynamics (MD) simulations and Poisson-Boltzmann calculations. The bilayer is composed of anionic palmitoyl-oleoyl-phosphatidylglycerol (POPG) and palmitoyl-oleoyl-phosphatidylethanolamine (POPE) with ratio 1:3 (POPG:POPE). PG1 is believed to kill bacteria by binding on their membranes. There it forms pores t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…However, Vivcharuk and Kaznessis (2010) showed that an AMP dimer has greater peptide-membrane attraction than the monomer counterpart. Therefore, we believe a plausible explanation for our findings is that a dimer/tetramer has a wider, highly positively charged ''carpet-like'' surface leading to increased binding.…”
Section: Discussionmentioning
confidence: 99%
“…However, Vivcharuk and Kaznessis (2010) showed that an AMP dimer has greater peptide-membrane attraction than the monomer counterpart. Therefore, we believe a plausible explanation for our findings is that a dimer/tetramer has a wider, highly positively charged ''carpet-like'' surface leading to increased binding.…”
Section: Discussionmentioning
confidence: 99%
“…3. The idea that counter ion release contributes significantly to biomolecular adsorption to a charged surface is well known in the literature, e.g., counter ion release has been shown to drive interactions between proteins and DNA 70 , as well as between peptides and charged lipid bilayers;71 however, as we show below, understanding these contributions on a deeper level allows for greater control over the molecular driving forces in adsorption and thus represents a new step towards rational design of the biomolecule/surface interface. Reweighting Analysis for the Number of Desorbed Ions.…”
mentioning
confidence: 99%
“…We computed PMFs for PG-1 monomer and dimer adsorption to lipid bilayers (3:1 POPE:POPG) [20], PG-1 dimerization in different environments (water, membrane surface, membrane interior) [21], and studied PG-1 monomer insertion into POPE:POPG lipid bilayers.…”
Section: Molecular and Cellular Models Of Amp Activitymentioning
confidence: 99%
“…Using atomistic models, we determined the dominant peptide orientations on lipid membranes. We found that electrostatic interactions and counterion release account for the low free energy of peptide-membrane binding [20]. …”
Section: Molecular and Cellular Models Of Amp Activitymentioning
confidence: 99%
See 1 more Smart Citation